Fabrication of magnesium-carbonate apatite by conventional sintering and spark plasma sintering for orthopedic implant applications - Setyadi, Iwan; Sudiro, Toto; Hermanto, Bambang; Oktari, Prima Rizky; Kamal, Achmad Fauzi; Rahyussalim, Ahmad Jabir; Suharno, Bambang; Supriadi, Sugeng (Penerbit Universiti Kebangsaan Malaysia, 2022)
Magnesium-Carbonate Apatite (Mg-xCA) is one of the potential magnesium composites to be developed as an alternative biodegradable implant material. Several attempts were made to optimize its characteristics. In this study, Mg-xCA (x = 0, 5, 10, and 15% wt) was prepared by powder metallurgy through warm compaction (WC) and further densified by 2 sintering process methods, namely conventional sintering (CS) and spark plasma sintering (SPS). The characterization included density test, XRD test, microstructure test (OM and SEM-EDS-Mapping), microhardness test, and electrochemical test. The SPS process improves the characteristics of Mg-xCA better than the CS process. The SPS process can increase the relative density by about 0.7-2.4%, increase the hardness by about 2-13%, and reduce the corrosion rate by about 32-49% compared to the initial condition before sintering (WC). The SPS structure has a lower oxygen elemental content than the CS structure. The sintered process with SPS is considered effective for the fabrication of Mg-xCA powder-based composites compared to the CS process.